1996
DOI: 10.1016/0550-3213(96)00426-9
|View full text |Cite
|
Sign up to set email alerts
|

The Landau-Pomeranchuk-Migdal effect in QED

Abstract: The calculation of the radiative energy loss encountered by a fast charged particle which undergoes multiple scattering is being investigated. A detailed derivation of the Landau-Pomeranchuk-Migdal coherent effect in QED is given, focusing on the specific feature of the Coulomb interaction. As a result the radiation intensity per unit length in the coherent regime is shown to be proportional to $\sqrt \omega$ for a photon energy $\omega$ times a logarithmic enhancement which is determined exactly.Comment: 19 p… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
185
1
1

Year Published

1997
1997
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 137 publications
(194 citation statements)
references
References 18 publications
6
185
1
1
Order By: Relevance
“…[16]. It was later demonstrated to be equivalent to the well known BDMPS approach [17]. The current, most widespread, variant of this approach developed by numerous authors is often referred to as the Armesto-SalgadoWiedemann (ASW) approach.…”
Section: Opacity Expansion: Path Integral Approachmentioning
confidence: 99%
“…[16]. It was later demonstrated to be equivalent to the well known BDMPS approach [17]. The current, most widespread, variant of this approach developed by numerous authors is often referred to as the Armesto-SalgadoWiedemann (ASW) approach.…”
Section: Opacity Expansion: Path Integral Approachmentioning
confidence: 99%
“…For soft photons (E ∼ gT , where g is the QCD coupling constant ), one needs to re-sum not only the propagators but also the dressed vertices. The detailed calculation of the soft photon rate, performed in [28], show that the Braaten-Pisarski re-summation does not lead to a finite result, free from mass singularities. Moreover, in [29] it was indicated that, the Braaten-Pisarski re-summed contribution is subleading, as there is a set of singular bremsstrahlung type diagrams which dominate the soft photon rate.…”
Section: Thermal Photon Yieldmentioning
confidence: 99%
“…As a result the radiation process becomes delocalized, with some characteristic number of scatterers being responsible for a single emission. This leads to a suppression of the radiation spectrum and a strong length dependence of the energy loss of the emitting parton [8,10]. This effect is believed to provide the dominant contribution to the observed suppression of leading hadrons.…”
Section: Introductionmentioning
confidence: 99%
“…We implement the LPM effect using a local MonteCarlo routine in the style of Zapp and Wiedemann [7], which reproduces the leading BDMPS-Z [8][9][10][11][12] result for light-parton energy loss in a QGP medium ∆E ∼ L 2 . This method is particularly appealing since it requires no artificial parametrization of the radiative process, it is a purely probabilistic medium induced modification.…”
Section: Implementing the Lpm Effectmentioning
confidence: 99%
See 1 more Smart Citation